Cytotoxic T Cell-Derived Granzyme B Is Increased in Severe Plasmodium Falciparum Malaria - Kaminski, Lea-Christina; Riehn, Mathias; Abel, Annemieke; Steeg, Christiane; Yar, Denis Dekugmen; Addai-Mensah, Otchere; Aminkiah, Francis; Owusu Dabo, Ellis; Jacobs, Thomas; Mackroth, Maria Sophia (Frontiers in Immunology, 2019)
In Plasmodium falciparum malaria, CD8+ T cells play a double-edged role. Liver-stage specific CD8+ T cells can confer protection, as has been shown in several vaccine studies. Blood-stage specific CD8+ T cells, on the other hand, contribute to the development of cerebral malaria in murine models of malaria. The role of CD8+ T cells in humans during the blood-stage of Plasmodium falciparum remains unclear. As part of a cross-sectional malaria study in Ghana, granzyme B levels and CD8+ T cells phenotypes were compared in the peripheral blood of children with complicated malaria, uncomplicated malaria, afebrile but asymptomatically infected children and non-infected children. Granzyme B levels in the plasma were significantly higher in children with febrile malaria than in afebrile children. CD8+ T cells were the main cell subset expressing granzyme B. The proportion of granzyme B+ CD8+ T cells was significantly higher in children with complicated malaria than in uncomplicated malaria, whereas the activation marker CD38 on CD8+ T cells showed similar expression levels. This suggests a pathogenic role of cytotoxic CD8+ T cells in the development of malaria complications in humans.